Effects of school-based physical activity on mathematics performance in children: a systematic review - S. Sneck; H. Viholainen; H. Syväoja; A. Kankaapää; H. Hakonen; A.-M. Poikkeus; T. Tammelin (BMC, 2019)
Abstract Background The benefits of physical activity (PA) on children's health and wellbeing are well established. However, the benefits of PA on academic performance and particularly on mathematics performance warrant systematic analysis. Mathematics is one of the core subjects in school education globally. Methods We systematically searched, analysed and synthesized the literature on the effects of school-based PA interventions on mathematics performance in children aged 4-16. A total of 29 studies consisting of randomised trials and other interventions with control groups were identified through a systematic search, and 11 of them provided sufficient data and appropriate design for a meta-analysis. Results Of the 29 studies involving 11,264 participants, positive overall effects of a PA intervention on mathematics performance were found in 13 studies (45%) and neutral overall effects in 15 studies (52%). Only one study reported a significant negative result for a subgroup of children in the first half of the intervention. In a risk-of-bias assessment, 12 studies had low, 17 moderate, and none had a high risk of bias. The meta-analysis of 11 studies suggested an overall small positive effect (ES = 0.23) of the interventions. Only one study in the meta-analysis indicated a negative effect in one of the intervention groups. Conclusions Adding PA to the school day may enhance children's mathematics performance or has no negative effects on performance. Several types of PA interventions can be recommended to be added to the school day.